Twelve Concepts of Salvation in the Bible Perspective - Nidin, Solihin Bin Nidin; Simanjuntak, Ferry; Harefa, Fatinaso; Deak, Victor (International Journal of Social and Management Studies, 2022)
- The history of human salvation was initiated by God. God created man in God's own image and likeness, God created man for the purpose of His glory. Humans were created based on the standards that exist in God both morally and spiritually. Humans are given the power to maintain and be representatives of God over the universe. Before the devil was cast on earth, the fellowship between humans and God was good, but when humans fell into the devil's trap and followed what the devil wanted at that time the human relationship with God was cut off and humans had to face the consequences of being cut off from the source of life and being in the shadows. - shadow of death. Soteriology (the doctrine of salvation) is the broadest subject in the Bible. This is because it covers all of eternity in both the past and the future. Salvation relates to all mankind through the sacrifice of the Lord Jesus Christ. Through this paper, the author explains twelve concepts of salvation from a Christian perspective.